Nexus Between Economic Development and Energy Poverty to Gain Energy Efficiency: Empirical Evidence From China - Anser, Muhammad Khalid; Yusop, Zulkornain; Abbas, Shujaat; Ali, Sajid; Ahmad, Munir (Frontiers in Energy Research, 2022)
Graphical Abstract